2006
DOI: 10.1186/1471-2261-6-25
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of connexin 43 using a retroviral vector improves electrical coupling of skeletal myoblasts with cardiac myocytes in vitro

Abstract: BackgroundOrgan transplantation is presently often the only available option to repair a damaged heart. As heart donors are scarce, engineering of cardiac grafts from autologous skeletal myoblasts is a promising novel therapeutic strategy. The functionality of skeletal muscle cells in the heart milieu is, however, limited because of their inability to integrate electrically and mechanically into the myocardium. Therefore, in pursuit of improved cardiac integration of skeletal muscle grafts we sought to modify … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 33 publications
2
22
1
Order By: Relevance
“…Indeed, binding sites for this family of transcription factors are also present on the EF1a promoter. 34 The use of these two promoters in combination in lentiviral vectors has been reported previously; 28,35 however, the possibility of promoter interference was not examined in these studies. Therefore, while gene expression was seen from both promoters, as is the case in our study, promoter interference effects may have gone undetected.…”
Section: Promoter Interference In Lentiviral Vectorsmentioning
confidence: 92%
“…Indeed, binding sites for this family of transcription factors are also present on the EF1a promoter. 34 The use of these two promoters in combination in lentiviral vectors has been reported previously; 28,35 however, the possibility of promoter interference was not examined in these studies. Therefore, while gene expression was seen from both promoters, as is the case in our study, promoter interference effects may have gone undetected.…”
Section: Promoter Interference In Lentiviral Vectorsmentioning
confidence: 92%
“…The polycations' transduction enhancer activity is highly cell specific. Alternative polycations, such as positively charged lipid dioctadecylamidoglycylspermine (DOGS), can be more effective than Polybrene for specific cell populations (Tolmachov, Ma et al 2006). Transduction efficiency can be further increased by a very unusual and poorly understood method called "spinfection".…”
Section: How To Enhance the Transduction Of Cells With Lentiviral Vecmentioning
confidence: 99%
“…There is evidence that increasing myoblast connexin 43 expression can improve functional integration Tolmachov et al, 2006). There are also multiple ongoing clinical trials with different attempts to use skeletal myoblasts to repair damaged heart muscle, with some positive effects reported (Dib et al, 2009;Haider et al, 2008;Siminiak et al, 2004).…”
Section: -Skeletal Myoblastsmentioning
confidence: 99%
“…Disadvantages of using MSCs and adipose-derived stem cells include the potential for a patient's disease state to affect their stem cell pool (Heeschen et al, 2004), and conflicting reports as to whether MSCs actually differentiate into cardiomyocytes (van der Bogt et al, 2009), or if any observed functional improvements are due to cell fusion and/or paracrine effects (Burdon et al, 2011). …”
Section: -Adult Bone Marrow Stem Cellsmentioning
confidence: 99%